Determinants of agricultural technology adoption under partial population awareness: the case of pigeonpea in Malawi - Franklin Simtowe; Solomon Asfawd; Tsedeke Abate (Agricultural and Food Economics, 2016)
There is exhaustive literature on technology adoption rates and the relationship between technology adoption and relevant socioeconomic and policy variables. Yet adoption estimates derived from the application of standard techniques such as the probit and tobit yield biased estimates. This paper applies the modern evaluation technique: the counterfactual outcome framework to data from about 400 households in Malawi to assess the patterns of diffusion and adoption of improved pigeonpea varieties and their determinants. We find the sample adoption rate of improved varieties to be 14 % while the potential adoption rate if the improved varieties were widely disseminated is estimated at 41 %. The adoption gap resulting from the incomplete exposure to the improved pigeonpea is 27 %. Moreover, adoption is also found to be high among female-headed households, older farmers and those with access to credit. The findings suggest that for increased adoption, there is need for increased involvement of extension workers is the dissemination of information about improved pigeonpea varieties, a robust pigeonpea seed system to increase seed availability to farmers as well as the need for improved access to credit.
Keywords: 330; Pigeonpea; Diffusions; Adoption; Average treatment effect; Malawi